Juridical analysis of the rights of workers who are terminated due to refusal of mutation in terms of law no. 13 of 2003 concerning labor manpower - Atika Sunarto; Stanley A. Efendi; Ali Adnan; Kelly Kelly (IHSA Institute, 2024)
Workers in Indonesia have the right to reject mutations, as stated in Article 32 paragraph (1) letter b of Labor Law No. 13 of 2003. This provision allows workers to refuse changes in employment conditions, including relocation, if these alterations violate employment agreements, company rules, or legal statutes. The research, following a normative approach and using secondary data sources, highlights that workers can refer to Articles 31 and 32 to assess the compatibility of mutations with existing regulations. Termination of employment, as defined in Article 1 Point 25 of the Labor Law, can occur due to specific events resulting in the cession of rights and obligations between workers and employers. Rejection of mutations may lead to termination, according to Article 161 of Law No. 13 of 2003, with a mandatory issuance of warning letters. Disputes can be resolved through the Industrial Relations Court or alternative mechanisms, including Bipartite, Tripartite, Mediation, Conciliation, and Arbitration. If out-of-court attempts fail, the Industrial Relations Court serves as the final resolution step, involving filing a lawsuit and examination procedures in the local court